Entropy bounds and isoperimetry - Bobkov, Serguei G. (Serguei Germanovich), 1961- (Memoirs of the American Mathematical Society, 2005)
Introduction and notations Poincare-type inequalities Entropy and Orlicz spaces $LS_q$ and Hardy-type inequalities on the line Probability measures satisfying $LS_q$-inequalities on the real line Exponential integrability and perturbation of measures $LS_q$-inequalities for Gibbs measures with super Gaussian tails $LS_q$-inequalities and Markov semigroups Isoperimetry The localization argument Infinitesimal version Proof of Theorem 9.2 Euclidean distance (proof of Theorem 9.1) Uniformly convex bodies From isoperimetry to $LS_q$-inequalities Isoperimetric functional inequalities Bibliography.